2018
DOI: 10.1590/0103-6513.20180009
|View full text |Cite
|
Sign up to set email alerts
|

Application of lean healthcare in hospital services: a review of the literature (2007 to 2017)

Abstract: Process reengineering methodologies have become an international management phenomenon (Waring & Bishop, 2010), as there have been a growing pressure on health services to increase their efficiency. To achieve this goal, health services have sought alternatives to traditional models, adopting methodologies for improving processes commonly used in the manufacturing sector, including lean manufacturing (Radnor et al., 2012). The lean methodology, originated at Toyota, and also known as the Toyota Production Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Additionally, reviews on LH provide thematic analyses [ 65 ], updates [ 44 ], and operational definitions [ 66 ]. Still others are focused on hospital waste management [ 67 ], the choosing wisely approach [ 68 ], sustainability [ 69 ], leadership and management [ 70 ], and safety and patient care [ 71 ]. To the best of our knowledge there is not a SR focusing on inpatient care and outcomes related to patient flow and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, reviews on LH provide thematic analyses [ 65 ], updates [ 44 ], and operational definitions [ 66 ]. Still others are focused on hospital waste management [ 67 ], the choosing wisely approach [ 68 ], sustainability [ 69 ], leadership and management [ 70 ], and safety and patient care [ 71 ]. To the best of our knowledge there is not a SR focusing on inpatient care and outcomes related to patient flow and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Among the literature on the applications of Lean Healthcare, studies in particular analyze how the process of Lean Healthcare was implemented in both national (17,18) and international (14,19,20) scenarios. The results of these studies and in many other reviews (4,16,19,21,22) showed the processes of implementing Lean Healthcare had many similarities based on an understanding of the processes involved in flows of patients, materials or information. The most common tools were visual management, spaghetti map, time and motion studies, value stream mapping (VSM), Kaizen principles, standardization, (17,18,23) process mapping (11,24) and semi-structured interviews, documentary analyses and nonsystematic observations (23).…”
Section: Lean Principles and Tools Usage In The Healthcare Fieldmentioning
confidence: 87%
“…[1] Indeed, critical care nurses should be value oriented to all care practices for MVPs in which they are challenged with providing safe, efficient and effective care practices. [15] However, lean evaluation is the step that precedes the lean implementation and sustainability process. Value stream map (VSM) is a lean strategy that documents the time for each process step and helps critical care nurses determining which steps in the care process add value to MVPs and which steps take up resources and time and incur cost without adding value.…”
Section: Introductionmentioning
confidence: 99%